2018
DOI: 10.1016/j.ijpddr.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of molecular markers of drug resistance in Plasmodium vivax from the border regions of Thailand in 2008 and 2014

Abstract: The prevalence of Plasmodium vivax is increasing in the border regions of Thailand; one potential problem confounding the control of malaria in these regions is the emergence and spread of drug resistance. The aim of this study was to determine the genetic diversity in genes potentially linked to drug resistance in P. vivax parasites isolated from four different border regions of Thailand; Thai-Myanmar (Tak, Mae Hong Son and Prachuap Khiri Khan Provinces), and Thai-Cambodian borders (Chanthaburi Province). Iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
56
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(83 citation statements)
references
References 42 publications
(76 reference statements)
17
56
7
Order By: Relevance
“…The increased rate of these mutations suggests that chloroquine resistance in P. vivax will become more common in the South Asia region where chloroquine has remained the first-line drug [39]. Our findings from clinical isolates from Southeast Asia were also similar to other studies in this location [5][6][7]16,40]. A clinical report of chloroquine-resistant P. vivax in a Thai pregnant woman indicated that recurrent parasites during Day 21 and 143 carried the double F976:L1076 mutation [40].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The increased rate of these mutations suggests that chloroquine resistance in P. vivax will become more common in the South Asia region where chloroquine has remained the first-line drug [39]. Our findings from clinical isolates from Southeast Asia were also similar to other studies in this location [5][6][7]16,40]. A clinical report of chloroquine-resistant P. vivax in a Thai pregnant woman indicated that recurrent parasites during Day 21 and 143 carried the double F976:L1076 mutation [40].…”
Section: Discussionsupporting
confidence: 87%
“…Tandem repeat variants found in the Pvdhfr gene locus have been described by different laboratories [26]; the typing of these variants in this study followed that of a recent Thai study from 2018 [7]. This group described three different tandem repeat variants found in the Pvdhfr gene sequence.…”
Section: The Prevalence Of Tandem Repeat Variants In the Dihydrofolatmentioning
confidence: 61%
See 3 more Smart Citations